MUSIC STREAMING ADOPTION AND DIGITAL PIRACY CASE STUDY: SPOTIFY - Riady, Reyhan; Aprilianty, Fitri (Journal of Business and Management, 2018)
Abstract. This paper analyze the piracy problem of music streaming, specifically Spotify, in Indonesia. Spotify is an application that provides music and video streaming, which can be found on some Operation System such as Android, Mac, and Windows. One of the goal of streaming music services is to reduce the amount of piracy, as Spotify claimed to be. As of December 2017, Spotify has 157 million users, with 71 million of them are paid users. Ironically, among 71 million Premium users, Spotify has approximately 2 million users accessing their Premium service illegally through unauthorized downloading and other forms of digital piracy. As Spotify just registered the company on the stock market on Tuesday, April 3rd 2018, it would be important to maintain their brand image by reducing piracy. Preventing unauthorized downloading and other forms of digital piracy has been a persistent challenge. Strategies based on deterrence, ethical arguments, or technical measures have been effective, but only to a limited extent. The main objectives of this research is to know whether the adoption of music streaming system in this case Spotify affects digital pirating intention. The data of this research is collected through survey method of 200 Spotify users and analyze by using SEM-PLS. The results shows that perceived ease of use and community facilitation enhance perceived usefulness and enjoyment, which in turns correlates positively towards purchase intention. It is also proven that attitude towards unauthorized downloading, perceived cost of product, peer pressure, and risk and penalties positively correlates with piracy intention.Keywords: Music streaming, Adoption, Digital Piracy, Spotify, SEM-PLS